1991
DOI: 10.1213/00000539-199106000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pH of Bupivacaine on Duration of Repeated Sciatic Nerve Blocks in the Albino Rat

Abstract: Tachyphylaxis has been ascribed to tissue acidification after repeated injections of acidic local anesthetic solutions. We studied the effect of pH on the duration of action of bupivacaine to determine the validity of this proposed mechanism of tachyphylaxis by injecting bupivacaine solutions adjusted to pH 4.2 or 6.8 into a surgically implanted system created to permit in vivo irrigation of rat sciatic nerves with local anesthetic. Tachyphylaxis developed at both pH values. The results fail to support the aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1
1

Year Published

1994
1994
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 4 publications
1
3
1
1
Order By: Relevance
“…The results of this clinical trial disclosed that there was no beneficial effect of alkalization of anesthetic solution in regard to increasing its duration of action. This came in agreement with the results of Backer et al (10) Several factors play a major role in increasing the duration of a dental procedure including the difficulty of operation, age of patient, size of lesion, number of teeth…..etc. The results showed no significant difference in regard to the duration of operation within the same group and between the two groups.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The results of this clinical trial disclosed that there was no beneficial effect of alkalization of anesthetic solution in regard to increasing its duration of action. This came in agreement with the results of Backer et al (10) Several factors play a major role in increasing the duration of a dental procedure including the difficulty of operation, age of patient, size of lesion, number of teeth…..etc. The results showed no significant difference in regard to the duration of operation within the same group and between the two groups.…”
Section: Discussionsupporting
confidence: 92%
“…(4,7,15) Another important criterion to which this clinical trial highlighted on was the highly possible pain experienced during the surgical procedure. Although several studies have stated that alkalization of local anesthetic solution did not improve the depth of anesthesia, (9)(10)(11)(12) the finding in the current study showed a significant enhancement in the depth of anesthesia which in turn is important for the full completion of a surgical procedure. This may be explained by the fact that in some studies, the anesthetic solution was injected into relatively normal tissue, (14,15) whereas in the current study, endodontic surgery was performed on infected tissue which of course will weak-en the anesthetic solution due to the acidic environment.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…Bromage et al described it as “a form of acute tolerance or tachyphylaxis, develops in response to repeated applications of LAs.”[ 28 ] Tachyphylaxis is established when the block is waning, and the noxious stimuli persists. [ 29 ]…”
Section: Tachyphylaxismentioning
confidence: 99%
“…The initial decline in duration is surprising, as a previous electrophysiologic groundwork showed a sub‐blocking long‐lasting decrease in excitability that could prolong the effect of subsequent blockades . However, one study investigating the duration of repeated sciatic nerve blocks in the rat using the long acting LA, bupivacaine, showed a similar pattern of nerve block duration …”
Section: Discussionmentioning
confidence: 99%